El Rincón InterCreativo. Número 74 - Uldarico Malaspina; Renzo Sandoval Quispe; Fernando Alejandro Alva Montañez; Gonzalo Landa Chávez; Guillermo Reyes Parra (UNIÓN - REVISTA IBEROAMERICANA DE EDUCACIÓN MATEMÁTICA, 2025)
Comentarios al problema del número anterior.